A contribution to the genus Steccherinum (Steccherinaceae, Polyporales): Introducing two new species and two new combinations of the genus - Liu, Zhan-Bo; Zhou, Meng; Zhang, Qiu-Yue; Si, Jing (Frontiers in Microbiology, 2023)
Two new wood-inhabiting fungi from China, Steccherinum juniperi and S. incrustans, in the family Steccherinaceae are described and illustrated based on morphological and molecular analyses. The species S. juniperi was found growing on the rotten wood of Juniperus in Qinghai Province, China, while S. incrustans was collected on rotten angiosperm wood in Yunnan Province, China. The characteristics of S. juniperi include annual, resupinate basidiomata with a buff yellow fresh pore surface that becomes apricot orange when bruised, angular pores of 3–6 per mm, subicular generative hyphae sometimes covered with crystals, the presence of encrusted skeletocystidia in tube trama only, fusiform to slim clavate cystidioles, and ellipsoid basidiospores measuring as 3–4 × 2–3 μm. The characteristics of S. incrustans include annual, resupinate basidiomata with a buff yellow or pinkish buff to clay buff dried pore surface, angular pores (8–10 per mm), generative hyphae in trama frequently covered with crystals, the presence of encrusted skeletocystidia in tube trama and hymenium, and ellipsoid basidiospores (3.5–4.5 × 2.5–3.5 μm). Phylogenetic analysis based on a combined 2-locus dataset [ITS1-5.8S-ITS2 (ITS) + nuclear large subunit RNA (nLSU)] shows that the two species are members of Steccherinum, and they are compared with morphologically similar and related species of this genus, respectively. In addition, two new combinations from Junghuhnia, transferred to Steccherinum as S. austrosinense and S. nandinae, are proposed based on examination of their type materials and phylogenetic analysis.